Sustainable and Inexpensive Polydimethylsiloxane Sponges for Daytime Radiative Cooling. Issue 23 (20th October 2021) - Zhou, Lyu; Rada, Jacob; Zhang, Huafan; Song, Haomin; Mirniaharikandi, Seyededriss; Ooi, Boon S.; Gan, Qiaoqiang
Abstract: Radiative cooling is an emerging cooling technology that can passively release heat to the environment. To obtain a subambient cooling effect during the daytime, chemically engineered structural materials are widely explored to simultaneously reject sunlight and preserve strong thermal emission. However, many previously reported fabrication processes involve hazardous chemicals, which can hinder a material's ability to be mass produced. In order to eliminate the hazardous chemicals used in the fabrication of previous works, this article reports a white polydimethylsiloxane (PDMS) sponge fabricated by a sustainable process using microsugar templates. By substituting the chemicals for sugar, the manufacturing procedure produces zero toxic waste and can also be endlessly recycled via methods widely used in the sugar industry. The obtained porous PDMS exhibits strong visible scattering and thermal emission, resulting in an efficient temperature reduction of 4.6 °C and cooling power of 43 W m −2 under direct solar irradiation. In addition, due to the air‐filled voids within the PDMS sponge, its thermal conductivity remains low at 0.06 W (m K) −1 . This unique combination of radiative cooling and thermal insulation properties can efficiently suppress the heat exchange with the solar‐heated rooftop or the environment, representing a promising future for new energy‐efficient building envelope material. Abstract : This work presents a porous polydimethylsiloxane (PDMS) sponge fabricated using a sustainable and inexpensive sugar‐template casting method. The obtained porous PDMS sponge exhibits efficient radiative cooling performance and excellent thermal isolation. This combined feature can suppress the heat exchange from warm outdoor environment, indicating its application for future energy‐efficient building envelope materials.